2010
DOI: 10.3997/1873-0604.2010041
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of magnetic and electrical resistivity surveys over simulated clandestine graves in contrasting burial environments

Abstract: It can be crucial to know the effectiveness of particular geophysical detection techniques when trying to locate clandestine burials of murder victims. . Unlike in archaeology, there has been limited forensic research with regard to optimum methodologies, with most emphasis to-date on metal detectors and Ground Penetrating Radar by forensic search teams. This may not be suitable in certain soil types, non-metal targets or in significant search areas. Therefore in this study, magnetic and electrical resistivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…For each grave, the overlying vegetation was removed and c. 2 m x 2 m holes were dug in a regular pattern (Fig. 2a) as other researchers have undertaken [46][47][48][49][50][51][52]. Soil from both the top and main andisol soil were taken from all graves for analysis.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…For each grave, the overlying vegetation was removed and c. 2 m x 2 m holes were dug in a regular pattern (Fig. 2a) as other researchers have undertaken [46][47][48][49][50][51][52]. Soil from both the top and main andisol soil were taken from all graves for analysis.…”
Section: Study Sitementioning
confidence: 99%
“…Recent geophysical research using simulated clandestine graves have found optimal detection methods and configurations are highly variable, depending upon a host of factors, the most important deemed to be time since burial, burial style, local soil type, vegetation and climate [35,[43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Their test site has been the subject of various decomposition studies and they are replicating the conductivity of decompositional fluid experiment [3]. They also have access to a woodland environment at Lincoln University that has been used for resistivity and magnetic survey studies [20], resistivity anomalies present even when surface remains are not obvious, thought to be decompositional fluids being retained in the local soil.…”
Section: Introductionmentioning
confidence: 99%
“…These have been repeatedly geophysically surveyed by fixed-offset electrical and Electrical Resistivity Imaging (ERI) surveys as well as multi-frequency (110-900 MHz) GPR datasets at least quarterly, and every month in the first three years post-burial. Studies have been published on determining what causes relative resistivity anomalies [19], magnetic surveys [20], measurements of decompositional fluid conductivities over time [3] as well as the 0-3 years post-burial datasets [6]. Repeat surveys suggest winter surveys are optimal and resistivity surveys should be undertaken six months to two years post-burial for optimal success.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation